Vulnerability in Consumption, Education, and Health : Evidence from Moldova during the Russian Crisis - Murrugarra, Edmundo; Signoret, Jose (World Bank, Washington, DC, 2014)
The authors analyze the widespread effects of the financial crisis in Russia to explore the vulnerabilities of households in Moldova. They show that the crisis had differential impacts on households, affecting most the urban and better-off. Households' decisions about education and health resulted in decreased utilization and expenditures. The enrollment of young children from better-off households did not improve while others did. Secondary school enrollment of children from better-off households decreased after the crisis, in part because of the need to release labor supply. Health utilization decreased mainly for primary health care (not for hospitals), both for better-off households and in rural areas. Some of these changes are due to limited household resources (health), decreased public spending (health and education) or the need to increase households' labor supply (education of teenagers). Social benefits played a very limited role in mitigating these effects, solely in health care use. Households' assets helped to offset some of the negative effects of declining incomes.